Trends in taxonomy of chagas disease vectors (Hemiptera, reduviidae, triatominae): From linnaean to integrative taxonomy - Chaboli Alevi, Kaio Cesar [UNESP]; de Oliveira, Jader [UNESP]; da Silva Rocha, Dayse; Galvão, Cleber (MDPI, 2021)
Chagas disease is a neglected tropical disease caused by the protozoan Trypanosoma cruzi and transmitted mainly by members of the subfamily Triatominae. There are currently 157 species, grouped into 18 genera and five tribes. Most descriptions of triatomine species are based on classical taxonomy. Facing evolutionary (cryptic speciation and phenotypic plasticity) and taxonomic (more than 190 synonymizations) problems, it is evident that integrative taxonomy studies are an important and necessary trend for this group of vectors. Almost two-and-a-half centuries after the description of the first species, we present for the first time the state-of-the-art taxonomy of the whole subfamily, covering from the initial classic studies to the use of integrative taxonomy.
Keywords: Classical taxonomy; Integrative taxonomy; Molecular taxonomy; Triatominae